DENGAN GANTI RUGI (PHGR) DENGAN MENGGUNAKAN AKTA NOTARIS ATAS TANAH GARAPAN (STUDI PUTUSAN MAHKAMAH AGUNG NO. 554PK/PDT/2014) - SALSABHILA - (PREMISE LAW JURNAL, 2017)
ABSTRACT Physical control on uncertified land causes dispute in society because its legal basis on the land is only a notification letter from the village head or subdistrict head. It even does not have any letter which becomes the evidence for the land physical control.The research used juridical normative and descriptive analytic method by analyzing legal provisions in land law, especially on the transfer of physical control on land through transact by using APHGR made a Notary. The result of the research shows that the legal domicile of making Notarial deed on the renunciation of rights by compensation is valid and has legal force. It is used as evidence on the transfer of physical control on uncertified land which can be used as authentic evidence to register the land in the local Land Office. The panel of judges consideration in the Supreme Court’s Ruling No. 554PK/PDT/2014 in the case of APHGR made by the Notary which is in dispute is that certified land cannot be transferred its right through an APHGR by a Notary because he only has the authority to make an APHGR on uncertified land. Keywords: Renunciation of Rights by Compensation, Notarial Deed, Tilled Land